Jeruk mangga / Muhammad Na’im Kamari - Kamari, Muhammad Na’im (2022)
Many vendors are afraid to take any more chances in order to maintain their business after the pandemic season, which has had such a significant influence on our society, and many merchants are claimed to have gone bankrupt during the epidemic. Modest businesses are also impacted, as they can only earn a small profit and must sell their products at a low cost. Following the conclusion of the third season of MCO, the Prime Minister stated that the business might be reopened, so I began looking for things to sell in order to earn money and purchase my own requirements. So, I decided to sell RM 13.00 worth ofJeruk Mapgga. Jeruk-Manqqa has grown in popularity in recent years, particularly among the youth. In addition, my estimates show that the teen population in my hometown is larger than the adult population. I also discovered that my area has University students. As a consequence, I armoptimistic that my company will function smoothly and according to plan.